(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the relationship between shock index when entering emergency surgery room with risk of hypotension postintubation and amount of tranfusion during surgery. Research objects and methods: 82 patients diagnosed with polytrauma (without traumatic brain injury and spinal cord injury) were admitted to the emergency operating room within the first 24 hours of injury. Record blood pressure when entering the operating room and after induction of anesthesia, blood volume, intraoperative fluid volume and calculate the predicted value through the area under the curve. Result: The cut-off of admission shock index predicted postintubation hypotension was 0.96 (sensitivity 94.12%, specificity 77.42%) and predicted massive tranfusion was 1.1 (sensitivity 81%, specificity 71%). The area under the ROC curves were 0.87 and 0.79, respectively. Conclusion: We found that shock index (SI) ≥ 0.96 as a good predictor of hypotension postintubation and shock index ≥ 1.1 as a predictor of massive tranfusion in operation.